The Role of Public Organizations in Ensuring National Security of Ukraine - Kovalova, Olena V.; Korniienko, Maksym V.; Pavliutin, Yurii V. (Cuestiones Políticas, 2020)
This article aims to identify the forms of participation of public organizations in national security. The basic methodological approach of the research is the analysis and generalization of the normative legal support and the scientific works that allowed to systematize and characterize the existing forms of participation of public organizations to guarantee the national security of Ukraine. The article emphasizes the importance of the influence of public organizations in the state of national security and the importance of a comprehensive and coordinated approach to involve public organizations in national security, generalizes and describes the forms of participation of public organizations to guarantee national security through the lens of the main forms of their interaction with the authorities of the organizations (information, control, consultation, active participation), the legal and organizational directions to strengthen the role of civil organizations in guaranteeing the National security. It is concluded that this type of research has practical value for representatives of the authorities and the public sector on possible ways to improve the role of public organizations to guarantee national security.